Comparison of physical characteristics and performance among elite snowboarders - Platzer, H. -P.; Raschner, C.; Patterson, C.; Lembert, S. (The Journal of Strength and Conditioning Research, 2009)
There are little scientific data regarding snowboarding and the physiological demands on snowboarders. The aim of this study was to assemble and evaluate a battery of tests for the snowboard disciplines parallel, snowboard cross (SBX), big air, and half-pipe (HP). Thirty-seven competitive snowboarders participated in the study and completed a test battery that comprised tests for aerobic capacity, balance, jumping, isokinetic core power, isokinetic leg power, isometric bench press, isometric bench pull, and a snowboard start simulator. The results showed that the battery of tests explained between 61 and 98% of variance when predicting snowboard performance. The test battery predicts better for women than for men and better for SBX, HP, and overall World Cup ranking than for the other disciplines. The results indicate that starting speed, leg power, core power, and aerobic capacity are important in different snowboarding events.